朝向一個創造「共好」的課程推展體系探究：機制建立與人才培育取向Toward a "Sharing Good" Curriculum Promotion Mechanisms: The Approach on System and Talent Cultivation - 陳美如 (通訊作者); 莊惠如Hui-Ju Chuang (Higher Education Foundation, 2012)
本研究旨在既有體系與正在建構的體系中進行理論的論述與實踐溝通。嘗試從理論與實踐現場的觀看與理解中找到可能性，並嘗試建構其可能的體系，更重要的是透過課程推展體系的建立，讓課程改革過程中的「人」，亦能得以開展，並將實踐歷程與智慧回饋至課程改革系統。為達成研究目的，本研究深入探討臺灣與國外當前的課程推展體系，並依據研究目的擬訂團體座談會討論題綱，根據當前困境、理想樣貌與具體配套措施三個層面與各個層級專家學者進行團體座談與諮詢會議，並佐以文獻與文件檔案分析，以瞭解課程推展體系中的組織與任務、組織間的關係與互動，以及策略配套與人才培育之內涵。歸納研究發現，提出以下結論與建議：一、課程推展不能僅限於課程推動自身，而是要與人發生關聯，課程推展的理念宣示溝通與發展人的核心關懷需要不斷提醒與落實，並與教育人員的成長共同思考實踐；二、課程改革推展體系中，其推展的關係並非單向，而是多向的生態體系，是相互連帶的，強調推展過程的溝通對話與互動；三、國家教育研究院是國家課程推動的大腦與引擎，需要進行組織內的調整，調用專業人員並需有專屬課程推展經費支持；四、將國家課程審議會設為常設性機制，能改善國家與民間課程改革缺乏共識之問題；五、透過實驗學校進行課程實驗與推展，以使課程改革內容更具可行性；六、師資培育機構為一協助單位，透過分區領導提供諮詢服務與進行人才培育；七、教師層級在課程推展體系中應發揮其主動性、主體性與更積極之功能；八、建立教師生涯發展階梯，營造一個教師間相互協力實踐與影響的環境。The purpose of this study is to theoretically describe and practically discuss curriculum promotion systems which are both in process and already in place. The study uses theory as well as practical observation to explore curriculum possibilities and look for other possible promotion systems as well. But most importantly, the study promotes the establishment of curriculum promotion systems to ensure the development of persons involved in the curriculum reform, and to ensure that practical experience and wisdom is integrated into the reform process. In order to achieve these aims, this paper thoroughly discusses current curriculum promotion systems in Taiwan and abroad. The study also employs seminars group discussions to investigate relevant issues, current problems, ideal models, and concrete measures. Specialist scholars at each of these three levels are invited to conduct seminars and advising sessions. The study will also thoroughly review relevant literature and documentation to adequately understand the organizational structure and responsibilities implicit in the curriculum promotion system, to understand the interactive nature of the organizational parts of the system, and to understand strategy and talent cultivation dimensions of the system. The Study's conclusions and recommendations are as follows: (1) Curriculum promotion doesn't limit in courses, but connects with person. The idea declaring, communication and core concern for staff development in curriculum promotion need to remind and implement constantly and developed amongst education workers. (2) In a curriculum promotion system, efforts are not uni-directional but rather multi-directional. The whole system can be thought of as its own ecosystem which is based on the mutual interaction of its members. As such, communication, dialogue and interaction are crucial for the development of the curriculum. (3) The National Academy for Educational Research is the nerve center and the main driving force behind the national curriculum. Adjustments need to be made to the organization, and specialized personnel and funding should support these projects. (4) The National Curriculum Review should act as a permanent mechanism which can promote a common understanding of curriculum reform at both government and citizen levels. (5) Experimental schools should be employed to experiment with and develop curriculum, making the contents of curriculum reform more feasible. (6) Teacher training institutions should play a supporting role administered through different districts, and should offer advising services and cultivate needed talent. (7) Teachers should play an active, central, positive role in the curriculum promotion system. (8) Build a life-long professional development system to cultivate a cooperation and practicing environment.